Survey study and experimental investigation on the local behavior of pedestrian groups. Issue 6 (18th November 2014) - Wei, Xiaoge; Lv, Wei; Song, Weiguo; Li, Xiaolian
<x xml:space="preserve">Abstract</x> Current research on pedestrian dynamics mainly focuses on the interactions among isolated individuals, the impact of the presence of groups is not fully considered. In recent 5 years, researchers have started to investigate pedestrian group movement. The aim of this work is to explore the local behavior of pedestrian groups by questionnaires and field observation. Survey study focused on pedestrians' psychology when walking in groups, which included five parts: group size, interpersonal distance, spatial relationship among group members, speed adjustment of group members, information transmission, and acid action among group members. Meantime a field observation was carried out to study group movement characteristics, which contained speed, step frequency, offset angle and interpersonal distance. The survey results show that group members have a closer interpersonal distance, faster information transmission and plenty of acid action. Conversely, group walking has a negative influence on pedestrian's speed, step frequency by comparing with the way isolated pedestrian walks. In addition, it is found that for a certain group, the group members are able to keep movement consistent. Also there exists obvious movement diversity among different group types (male dyads, female dyads, couple groups, and ordinary‐friend groups) because of different gender and social relationship. Ultimately the results will be more promising for helping to model the movement of pedestrian groups. © 2014 Wiley Periodicals, Inc. Complexity 20: 87–97, 2015